Divergent mechanisms of acoustic mate recognition between closely related field cricket species (Teleogryllus spp.). (August 2017) - Bailey, Nathan W.; Moran, Peter A.; Hennig, R. Matthias
Abstract : Effective recognition of conspecific mating signals reduces the risk of maladaptive hybridization. Dissecting the signal recognition algorithms that underlie preferences is a useful approach for testing whether closely related taxa evaluate the same or different signal features to achieve mate recognition. Such data provide information about potential constraints and targets of selection during evolutionary divergence. Using a series of mate choice trials, we tested whether closely related, but genetically and phenotypically divergent, field cricket species ( Teleogryllus oceanicus and Teleogryllus commodus ) use shared or distinct recognition algorithms when evaluating acoustic male calling songs. These species overlap in sympatry, show premating isolation based on female discrimination of male calling songs, yet are capable of producing hybrid offspring. Unexpectedly, female selectivity for features of male song differed between the two species. We found that the two species use a combination of shared and unique signal filtering mechanisms, and we characterized how information about male carrier frequency, pulse rate and temporal patterning is integrated to achieve song recognition in each species. These results illustrate how comparatively few, simple modifications in key components of signal recognition algorithms can lead to striking interspecific discrimination between closely related taxa, despite apparent signal complexity. The finding that some steps during signal recognition and filtering are shared between the species, while others differ, can help to identify behavioural traits targeted by selection during evolutionary divergence. Highlights: How do animals recognize complex signals from conspecifics? We tested how females of field cricket sister species evaluate male song. The species used a mix of shared and different signal recognition mechanisms. Different perception and weighting of song features evolved via simple switches. Divergence in mate recognition follows evolutionary 'paths of least resistance'.